THE EFFECTS OF ENCOURAGEMENT ON LEARNING: HOW ENCOURAGEMENT AFFECTS THE QUALITY OF STUDENTS’ PROGRESS DURING LEARNING LANGUAGE - Cakra Sagiarta Lee; Putu Chrisma Dewi; Ni Luh Christine Prawita Sari Suyasa; Putu Chris Susanto (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
The main purpose of this study is to investigate the effectiveness of encouragement on the quality of the students’ learning progress during German learning. This research utilizes the mixed method of quantitative and qualitative as data gathering method. The case study that this study observes is the language preparation of the 9 (nine) selected students for student exchange program from SMPK 2 Harapan (Junior High School) Bali under blended learning. It focuses on analyzing the students’ German learning progress both from their macro-skills and their inhibitions’ factors. Throughout the study, it gives also encouraging feedback to every of the students and tries to help the students to cope with their inhibitions’ factors. It takes interests in analyzing the effects of encouragement to students’ self-efficacy which affects their motivation to learn foreign language and the effects on their scores based on the 4 (four) macro-skills.